Enhancing Muslim SME Sustainability in Malaysia: The Role of Zakat and Financial Literacy - Daud, Dasyarini; Azhar, Zubir; Kishan, K.; Esa, Mohd Suffian Mohamed (Muslim Business and Economics Review, 2025)
Financial literacy issues pose significant challenges for small and medium enterprises (SMEs) in Malaysia, leading to improper financial management practices and poor performance. In response to these challenges, this study explores the potential role of zakat, an Islamic fiscal tool, in addressing financial management issues among Muslim SMEs. Specifically, the study analyses how zakat can serve as a mechanism for distributing assistance to poor Muslim entrepreneurs within the SME sector. Motivated by zakat's potential to mitigate financial management and literacy issues, this research employs semi-structured interviews to gather insights from seven Muslim entrepreneurs. Through qualitative analysis, the study examines the perceptions, experiences, and expectations surrounding zakat as a means of financial support tools for SMEs. The findings shed light on how zakat institutions can contribute to enhancing financial literacy and promoting sound financial management practices among Muslim SMEs, including the formulation of a proposed model of Non-Cash Zakat Distribution for Financial Management Services. The implications of this study extend beyond the immediate context. By effectively leveraging zakat funds, policymakers, financial institutions, and zakat administrators can play a proactive role in supporting Muslim SMEs and promoting grassroots economic development.